Implementasi Alat Monitoring Kesuburan Lahan Pertanian Ketela Pohon berbasis Web - Fathul Abdillah Khosin; Mochammad Hannats Hanafi Ichsan; Edita Rosana Widasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Cassava is a plant that can be used as a substitute for the daily staple food. Many farmers encounter obstacles at the time of post-harvest cassava, which is not suitable for harvesting for consumption. Most farmers do not know the fertility of the land to be planted. Implementing a monitoring tool on the system for observing the fertility of cassava agricultural land can be a solution. The method used is the Telemetry method. Where Telemetry is the process of measuring the parameters of an object (objects, space, natural conditions) whose measurement results are sent to other places via cables or without using cables (wireless). Telemetry is expected to provide convenience in measurement, monitoring and reduce barriers to obtaining information. Sensors are connected to components, then these components will be connected to each other through communication in the sensor network. From the implementation of the test, the results obtained from the test were that the tool worked properly where the monitoring tool could retrieve data from the research place where the sensor was installed. Then the monitoring tool can also send data to the webserver and the webserver successfully receives data from the monitoring tool and then saves it to the database on phpMyAdmin and displays it on the web pc or cellphone. Performance is obtained based on throughput, packet loss and delay with the result that the throughput is 8,567 kbps. The packet loss of is 0.1%. The total delay is 4.449 s and the average delay is 1.6322 ms.